Vacuum ultraviolet photodissociation of OCS via the 21Σ+ state: the S(1D2) elimination channel. Issue 29 (19th July 2022) - Li, Zheng; Liao, Hong; Yang, Wenshao; Yang, Xueming; Yu, Shengrui
Abstract : We report the dissociation dynamical characteristics and mechanism of the CO( 1 Σ + ) + S( 1 D2 ) channel via the 2 1 Σ + state. Abstract : The photodissociation of OCS is necessary to model the primary photochemical processes of OCS in the global cycling of sulfur and interstellar photochemistry. Here, by combining the time-sliced velocity-map ion imaging technique with the single vacuum ultraviolet photon ionization method, we have studied the CO( 1 Σ +, v ) + S( 1 D2 ) photoproduct channel from the OCS photodissociation via the eight different vibrational resonances ( = 1–8) in the 2 1 Σ + (, 1, 0) ← X 1 Σ + (0, 0, 0) band. From the measured S( 1 D2 ) images, the wavelength-dependent CO( 1 Σ +, v ) vibrational state populations have been obtained in the wavelength range of 142.98–154.37 nm. The majority of the CO( 1 Σ +, v ) photoproducts are shown to abruptly populate from low vibrational states to high vibrational states as the photolysis wavelength decreases from 152.38 to 148.92 nm. The anisotropy parameters ( β ) for the CO( 1 Σ +, v ) + S( 1 D2 ) channel have also been determined from the images of the S( 1 D2 ) photoproducts. It is found that the vibrational state-specific β -values present a similar decreasing trend with increasing CO vibrational excitation for all the eight vibrational resonances of OCS*(2 1 Σ + ). These observations indicate that there is a possibility that more than one non-adiabatic dissociation pathways with different dissociation lifetimes are involved in the formation of CO( 1 Σ + ) + S( 1 D2 ) photoproducts from the initial vibronic levels of the 2 1 Σ + state to the final dissociative state.